Fetomaternal Outcome in Pregnancy With Cardiac Disease (Journal of Chittagong Medical College Teachers' Association, 2012)
Aim of our study was to see the maternal and fetal outcomes in women presenting with heart disease during pregnancy and labout. This cross sectional study was carried out in 48 pregnant women with cardiac disease from July 2005 to Dec 2006, in the department of Gynae and Obst at Chittagong Medical College Hospital Chittagong. The Mewan age was 25.40 ±4.46 years. 31(64.6%) patients were from middle class. 27 (56.3%) patients belonged to mulliparous group. 33(68.8%) patients received regular antenatal care, of the 43 (89.7%) patients had rheumatic heart disease and 5(10.5%) had congenital heart disease. Among the rheumatic heart disease, 50% had mitral stenosis. 35(72.9%) patients had in grade-1, 12(25%) had in grade-II, and 1(2.1%) had in grade-III. (64.5%) had normal vaginal delivery, 7(14.5%) had LSCS. 4(8.3%) had heard failure and 1 patient (2.1%) expired due to heart failure, 40(83.3%) were delivered at term, 7(14.6%) had preterm labour and 1(2.1%) had still birth. Regarding birth weight, 17(35.4%) had LBW (Low birth weight), 31(64.6%) had normal birth weight. Rheumatic heart disease is the commonest cardiac lesion among Pregnant women. Fetomaternal morbidity and mortality are strongly correlated with maternal cardiac functional classification. The management of these cases should be multidisciplinary to optimize care of these patients.JCMCTA 2012; 23(1): 31-35